자치경찰제 도입을 고려한 해양경찰조직의 재구조화- 국가와 자치경찰간의 기능과 사무배분을 중심으로 - 윤희중 (한국해양경찰학회보, 8(2), 2018)
최근 문재인 정부는 국정과제로 자치경찰제의 로드맵을 발표하면서 논의를 확산시키고 있다. 하지만 자치경찰제에 대한 연구는 육상경찰 위주로 진행되어 왔으며해양경찰에 관한 논의는 미약하다. 이러한 상황에서 이 연구는 자치경찰제 도입을고려하여 국가와 자치경찰간 기능과 사무배분에 초점을 맞추어 해양경찰조직을 재구조화하는데 목적을 두고 있다. 우선 선행연구를 토대로 경찰제도의 유형과 통합형 관점에서 국가와 자치경찰의관계전략을 살펴보고 국가경찰과 자치경찰의 사무처리에 대해 개관해 보고자 한다. 그리고 2017년에 개편된 해양경찰 조직의 기능과 국가해양경찰 및 자치해양경찰의기능을 정리한 후, 새로운 국가해양경찰과 자치해양경찰의 구조모형을 제시하고 해양경찰 기능의 관점에서 국가와 자치해양경찰간의 사무배분을 재검토해 보려고 한다. 이러한 논의는 지식정보화 사회와 거버넌스 패러다임으로 전환하는 시점에서 탄력적으로 대응해야 하는 과제인데, 우리나라의 현 단계에서 자치해양경찰은 국가경찰과 자치경찰이 상호 협력하는 통합형 모델이 바람직하며 광역자치단체를 기준으로실시하는 것이 현실적이다. 자치해양경찰제 도입을 위한 추진방향은 제주특별자치도에서 시범적으로 운영한 후에 공론화 과정을 거치면서 재설계해야 하며, 위원회의 기능을 충실하게 이행할 수 있는 정책대안 모색도 심도 깊게 이루어져야 한다. 한편, 우리나라 해양경찰의 사무는 포괄적으로 명시되어 있기 때문에 해양경찰법을 마련하여 사무배문 내용을 구체적으로 규정하고, 그 규정을 작성할 때에는 해양경찰 조직의 인력과 재정뿐만 아니라 특정지역의 상황을 검토하여 실현가능성을 평가해야 한다. Recently the Moon Jae-in Government has been increasing discussion how to push ahead with the municipal police system after it announced roadmap of national political agenda. But studies of the municipal police system revolved around the land police rather than the coast guard in the Korea. In these situations, the purpose of this study is to restructure the Korea Coast Guard(KCG) organization for the introduction of the municipal police system, focusing on the function and affairs division between central and local police. First, Based on the precedent study, this study will take a look at the relationship strategies between the national police and the municipal police from the type of police system and the view of intergration. And then will provides an overview of the affairs that the national police and the municipal police handled. Second, this study will come up with the function of the national police and the municipal police. as well as the function of the KCG organization in 2017. Subsequently, it will present the structural model of the national police and the municipal police, Finally, this study will review affairs division of the national police and the municipal police from the functional perspective of the KCG organization. At turn in Knowledge and information society as well as governance paradigm, these discussions are the subject to respond flexibly. Integration model to collaborate with the national police and the municipal police is desirable for the autonomous KCG to leap at the current stage in Korea. And the reality is that it is to implement Integration model based on Wide-area Autonomous Communities. After a test trial by the Jeju Special Self-Governing Province, the autonomous KCG policy should be redesigned as a result of published processes. In this regard, the government needs to introduce policy alternatives to faithfully carry out the function of the committee. The affairs of the KCG, meanwhile, are comprehensively specified. Therefore, Specific contents of affairs division should be provided for by Coast Guard Law. When the government create the rules, it should be assessed the feasibility against the situation in specific regions as well as staff and finance of the KCG oranization. KCI Citation Count: 3